An Experimental Study of the Addition of Air Mass Flow Rate Using a 30% Emulsion-Fueled Diesel Engine at High Load - Rosid Rosid; Bambang Sudarmanta; Lukman Atmaja; Salih Özer (Automotive Experiences, 2020)
The purpose of this study was to examine the addition of air mass flow rate into the combustion chamber using E30 emulsion fuel (Water 70% + Dex 30% + 2% surfactant tween 80 + span 80 ) on a Diamond DI 800 stationary diesel engine with an engine rotation of 1500 rpm. Characteristics evaluated using Combustion Analyze, and emissions measured with a Gas Analyzer. The results showed the addition of air mass flow rate affected engine performance and emissions with the engine power observed to have decreased by 0.016% while SFC and thermal efficiency increased by 2,077% and 33,053% respectively compared to diesel fuel. Moreover, the BMEP and exhaust temperature also decreased with the most optimum in BMEP found to be 0.02% and exhaust temperature at 285°C while diesel has 358°C. The analysis of the combustion process for E30 emulsion fuel with variations in the air mass flow rate added showed the peak cylinder pressure at high loads was at 0.018 kg/s at a pressure of 5.86 bar. Meanwhile, the optimum heat release rate at high loads was obtained at a variation of 0.013 kg/s. This, therefore, means adding air mass flow rate to the E30 emulsion fuel has the ability to improve performance and reduce engine emissions.